Debris Index before and after gargling with moringa leaves - Putri, Zahra Aulia; Lestari, Syifa Yulia; Ngatemi, Ngatemi (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: Dental and oral hygiene is one of the factors that trigger dental caries. Preventive efforts can be made to anticipate oral health problems, one of which is gargling. The chemical mouthwash ingredient that is often used is chlorhexidin, while if used for a long time it can cause side effects in the form of bacterial resistance and discomfort. Therefore, the need for natural ingredients to minimize side effects that can arise cheap, safe and effective natural ingredients for gargling, one of which is moringa leaves. Objective: The purpose of this study was to determine the debris index before and after gargling with moringa reduce water in TPQ Al-Barokah Bojonggede students in 2024. Methods: This research method is quasi experiment research. This study was conducted with a sample of 30 students obtained using purposive sampling technique. The instrument used was the debris index examination sheet. Results: The difference of the debris index score before and after gargling with moringa reduce water is 0.43. With an average debris index score before gargling is 1,56 and the average debris index score after gargling is 1,13. Conclusion: It can be concluded that after gargling with moringa reduce water can reduce the debris index score.